Ideologia neoliberal e sistema punitivo - Pardal, Rodrigo Francisconi Costa (2023)
This thesis aims to analyze the relationship or relations between the neoliberal ideology and the punitive system from a critical perspective. The research is justified given the peculiarities that ideologically this form of rationality entails in the scope of punitive power. The Brazilian punitive model is analyzed from a technicist heritage in order to question its real scientific character and unveil the discourse of a supposed “neutrality”. The analysis of the word “ideology”, understood for the purposes of this work as blocking the meanings, is presented as a form of systemic and symbolic violence. It also discusses the formation of neoliberal rationality, its characteristics, as well as contradictions and how such a model of formation of subjectivities acts, alongside technicality, forming a new grammar of legal education. Next, the relationship between neoliberalism and the punitive system are analyzed, in order to carry out a critical analysis of the possibility of coupling such constructions to the Brazilian reality. Finally, it is verified that the ideology acts as a model based on a rational/irrational dialectic contextualized in a society predominantly of control that generates and fosters constant levels of resentment, factors that justify, legitimize and feed back the punitive system. Thus, it is verified that the neoliberal ideology, as a specific phase of capitalism, brings a qualitatively and quantitatively distinct formatting and with specificities that have repercussions in the discursive and practical scope of the punitive system. To this end, deductive, dialectical and dialogical methods are used